DEVELOPING AN EXTRUDER FOR MAKING 3D PRINTER FILAMENT AS A STEAM PROJECT - Kurmangaliyeva, Н.А.; Yersin , М.Е.; Kamalova, Г.Б.; Seiduali, Қ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article discusses the experience of implementing a STEAM project on the development of an extruder for recycling plastic bottles through its integration into the higher education system. As part of the research, a plastic recycling extruder for the production of 3D printer filament was developed. The main focus was on integrating engineering, technological and pedagogical aspects that allow combining scientific knowledge, digital skills and creative thinking of students. The development of an extruder is considered not only as a technical task, but also as an educational tool that forms competencies in the field of 3D modeling, digital control of parameters and sustainable development. During the study, the technical characteristics of the device were analyzed, experiments on filament production were conducted, and the effective educational effect of using digital tools for data processing and visualization was assessed. The results justify that the implementation of such projects contributes to the development of digital literacy, teamwork and practice-oriented skills that are in demand in modern society.